Do we feel the same emotions in simulation as with a real patient? A pilot study among dental students - Marion Strub (BMC Medical Education)
Abstract Introduction Simulation is an educational tool for developing the technical and nontechnical skills of dental students. To optimize learning in simulations, students must be immersed in a high-fidelity environment and emotionally engaged, as is the case in clinical practice. The primary objective of this study was to assess emotions during simulation training and in clinical practice. A commonly practiced procedure, dental extraction, was used as a guideline for this work. Materials and methodology A self-administered questionnaire related to the emotions experienced by the dental students was completed immediately after each dental extraction was performed in the clinic or simulation. The clinical case was a pediatric patient. Results The emotions experienced in the simulation were similar to those experienced by a student during clinical practice. Students enjoy caring for their patients but lose their composure more easily with difficult children. The students reported being more stressed and having difficulty communicating with younger patients. They acknowledged that their emotions could sometimes influence their care of the patient. Discussion Emotions can influence clinical decision-making. On the other hand, the role of emotions in learning must be considered by teachers so as not to discourage students. Teachers must balance exposure to emotionally charged situations with a method that is conducive to learning. Conclusion Simulation helps train students in clinical practice and can include the same range of emotions.